Nancy Drew. Season one [videorecording (DVD)] - Landau, Noga; Schwartz, Josh, 1976-; Savage, Stephanie (Nancy Drew (TV series : 2019- ), 2020)
Nancy Drew (Kennedy McMann) is a brilliant teenage detective whose sense of self had come from solving mysteries in her hometown of Horseshoe Bay, Maine - until her mother's untimely death derails Nancy's college plans. Devastated by her mother's passing, Nancy swears off crime-solving while crossing off the days until she can re-apply to college. But when a socialite is murdered, Nancy finds herself a prime suspect in the crime, along with a group of other teens present at the scene.